Untangling the Environment: Values and Affects Associated with Animals by Students of Psychology in Buenos Aires, Argentina - Díaz, Rocío Alejandra; Sánchez, Federico; Sevillano, Verónica; Cassini, Marcelo Hernán (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
The environment has traditionally been considered as a unitary entity without paying attention to the different elements that compose it (soil, water, atmosphere, flora, fauna and the processes that interrelate them). For this reason, the assignment of biocentric or anthropocentric motivations to people has been made in relation to the global environment. This research pays attention to one of the elements of the environment, animals, which has been neglected in environmental concern studies. Biocentric responses were more prevalent in opinions about zoos than in opinions about environmental issues. This positive assessment of animals is qualified when considering the responses on preference, fear and disgust for different animal species: (i) mammals are preferred and arthropods are rejected (comparison between taxonomic groups); and (ii) exotic species absent from Argentina ecosystems are preferred, and common species are rejected. The role that the empathic processes is discussed.